TIA-942 Approach dengan Computational Fluid Dynamic untuk Data Center - Sidabutar, Jeckson; Priambodo, Dimas Febriyan (Teknik Informatika Universitas Pamulang, 2021)
Data Center (DC) is currently one of the most popular Information and Communication Technologies (ICT) along with the increasing digitization of business processes. The concept of centralization provides convenience for the improvement, development and efficiency of energy resources. DC networks support cloud-inspired environments that require stability and agility, thereby extending the functionality of DC networks into a public cloud provider infrastructure to better manage hybrid cloud networks. The TIA-942 standard allows DC designs to be considered early in the building development process and contributes to architectural considerations, by providing multidisciplinary design and construction information. It is used for a comprehensive understanding of DC design including facility planning, cabling systems, and network design. Good planning during building construction or renovation is significantly less expensive and less intrusive than after the facility is operational. The DC design using the TIA-942 standard was tested through Computational Fluid Dynamic simulation to produce a better analysis. All of these analyzes are to avoid misplacing or positioning cooling devices or racks in the DC, as well as assisting in the selection of efficient cooling system technology. So that the DC design can function as an operation center and service provider, as well as increase efficiency and energy resources for all SKPD in XYZ Province.